2015
DOI: 10.1249/mss.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Training on Obese Adolescents

Abstract: RT alone improved endothelial function, hemodynamic and metabolic profiles, body composition, and physical fitness in nondiabetic obese adolescents regardless of changes in body mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
81
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 40 publications
6
81
0
1
Order By: Relevance
“…Generally, resistance training (RT) changes body composition without alterations in body weight of both lean and obese subjects (Dias et al ., ). RT changes the vascular system in concert with alterations in body fat in obese/overweight patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Generally, resistance training (RT) changes body composition without alterations in body weight of both lean and obese subjects (Dias et al ., ). RT changes the vascular system in concert with alterations in body fat in obese/overweight patients.…”
Section: Introductionmentioning
confidence: 97%
“…RT changes the vascular system in concert with alterations in body fat in obese/overweight patients. In both obese adolescents and in older men, RT improved endothelium‐dependent vasodilatation after ACh (Dias et al ., ) and increased femoral artery blood flow, microvascular blood flow and volume of the vastus lateralis muscle (Phillips et al ., ). However, data on the influence of different exercise characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the five included studies, three RCTs (Alberga, Farnesi, Lafleche, Legault, & Komorowski, 2013;Kelly et al, 2015;Schranz, Tomkinson, Parletta, Petkov, & Olds, 2014), one NRCT (Dias et al, 2015) and one UCT (Shultz et al, 2015) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the importance of a healthy skin microcirculation in avoiding digital ulcers, our findings suggest that there is an urgent need for further work in the field. Likewise, resistance training (RT) alone has shown significant improvements in the function of the vasculature [10], while a combination of aerobic and RT have shown both in the past [11] and recently [12] to significantly improve the vascular function and the microcirculation. However, the overall number of studies that have investigated the effects of RT on vasculature indicates remain.…”
Section: Introductionmentioning
confidence: 99%